A comparison of ghrelin, glucose, alpha-amylase and protein levels in saliva from diabetics - Aydin, Suleyman (Springer Singapore Pte Ltd, 2007)
During the past decade, many salivary parameters have been used to characterize disease states. Ghrelin (GAH) is recently-discovered peptide hormone secreted mainly from the stomach but also produced in a number of other tissues including salivary glands. The aim of this work was to examine the relationship between active (aGAH) and inactive (dGAH) ghrelin in the saliva and other salivary parameters in type It diabetic patients and healthy controls. Salivary parameters were assessed in a single measurement of unstimulated whole saliva from 20 obese and 20 non-obese type II diabetes patients, and in 22 healthy controls. Total protein and alpha-amylase were determined by colorimetric methods, and glucose by the glucose-oxidase method. Saliva aGAH and dGAH levels were measured using a commercial radioimmunoassay (RIA) kit. Salivary concentrations of aGAH and dGAH ghrelin were more markedly decreased in obese diabetic subjects than in the two other groups. Glucose and alpha-amylase levels were higher in diabetic subjects than in controls. Furthermore, there were correlations between GAH levels and BMI, and between GAH and blood pressure. However, there was no marked variability in saliva flow rates among the groups. These results indicate that measurement of salivary GAH and its relationship to other salivary parameters might help to provide insight into the role of ghrelin in diabetes.
Keywords: active/inactive ghrelin; alpha-amylase; diabetes; saliva